Development of Project-Based Learning e-Lkpd in Increasing Students' Interest in Learning in Mathematics Subject for Grade III SDN 1 Maria - Aisah, Nurul; Khatimah, Husnul; Kurniawan, Edy (FKIP - Universitas Riau, 2025)
This study aims to design and implement instructional materials in the form of a Problem Based Learning (PBL) based electronic Student Worksheet (e LKPD) to enhance learning interest among third grade students at SDN 1 Maria. The focus of the research is mathematics, specifically whole numbers up to 1.000. The research employed a Research and Development (R&D) approach using the ADDIE model, comprising five phases: Analysis, Design, Development, Implementation, and Evaluation. Validation results revealed that the media received an average score of 78.6 % in the first phase and 94.6 % in the second phase. Material experts yielded an average validation score of 83.6 % in the first phase and 92.7 % in the second phase-indicating that the e LKPD is highly suitable for instructional use. During the implementation phase, teacher responses averaged 94.4 % and student responses averaged 94.7 %, demonstrating that the e LKPD is very practical to apply. The effectiveness of the e LKPD was assessed through an N Gain test, comparing pre test and post test scores. The average N Gain score was 0.84, categorized as High. In conclusion, the PBL based e LKPD is considered highly feasible, practical, and effective as a teaching medium to enhance students’ learning interest.